The Renaissance of Shi'i Islam Facets of Thought and Practice - Esots, Janis; Daftary, Farhad (Shi'i Heritage Series, 2022)
The renaissance of Shi'i Islam began in the 9th/15th century when the Ismailis experienced the Anjudan revival and Twelver Shi'i traditions were also renewed. This renaissance gained further strength when the Safavids succeeded in establishing a state in the early decades of the 10th/16th century, making Ithna'ashari Shi'i Islam their official religion. The chapters in this open access book represent the most recent scholarship on the intellectual and spiritual life of the age and discuss what prepared the ground for its appearance as well as its achievements. Although the political and artistic developments of the Safavid era of the 10th-12th/16th-18th centuries have been extensively studied, the complexities of the different groups, movements and strands of thought in the renaissance of Shi'i Islam still remain largely unexplored. The major themes that characterised the Shi'i renaissance are explored, including: popular reactions to messianic movements; the development of legal theories and concepts; the investigation of theological and philosophical problems, above all by the 'School of Isfahan'; Shi'i-Sufi interactions and intra-Shi'i relations; the collection of Shi'i hadith and its application in Shi'i exegesis; and the interplay between political considerations and religious beliefs. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by The Institute of Ismaili Studies.